CANAL WATER SUPPLIES WARI CITY, AYACUCHO: CONSTRUCTION PROCESS AND COMPONENTS OF FUNCTIONALITY - Pérez Calderón, Ismael (2012)
The rationale of this paper is to report by presenting data on the direct recognition of the canal that supplied water for over three hundred years to the city of Wari, from investigations with excavations in several sections of the channel, as a reference for qochas work, canals, reservoirs supplying the metropolis Wari (Perez 2006, 2007 and 2010) and as part of the hydrologic and hydraulic study of inca canal Wari Wari Yarccan or Yarcca in Ayacucho (Chavarría 2010). We believe that this is a great proyec for social and economic infraestructure that the Wari state executed in the Andes during the second half of the first millennium od the present Christian era, about 800 yerars before formation of the Empire of Tawantinsuyo.